Hindu law Ed 25 - Dinshaw Fardunji Mulla; Desai, Satyajeet A (Haryana LexisNexis, 2024)
journey of twenty-five editions, spanning over a period of more than a hundred years, speaks volumes about this iconic legal classic. This tome has, since its inception, traced the origins, development and periodic changes that have taken place in the field of Hindu Law. Time and again, this seminal work has been relied upon by the Bench and the Bar, and its mention can be found in numerous important judgments of the Supreme Court and the High Courts. The book is divided into two parts: Part 1 of the commentary deals with customary Hindu Law, and Part 2 contains section-wise commentary on four major enactments: The Hindu Marriage Act, 1955, The Hindu Succession Act, 1956, The Hindu Minority and Guardianship Act, 1956, and The Hindu Adoptions and Maintenance Act, 1956.
Keywords: law